Levels and degradability of crude protein in digestive metabolism and performance of dairy cows - Alves, Bruna Gomes; Martins, Cristian Marlon de Magalhães Rodrigues; Sousa, Dannylo de Oliveira; Arcari, Marcos André; Rennó, Francisco Palma; Santos, Marcos Veiga (Brazilian Journal of Veterinary Research and Animal Science, 2020)
Two experiments were conducted to evaluate the effect of the level and degradability of crude protein (CP) on the digestive metabolism and productive performance of dairy cows. In both experiments, 15 Holstein cows with 585 ± 40 kg of body weight were distributed in a Latin square design with five contemporary squares, three periods of 21 days and three treatments. In experiment 1, treatments consisted of three CP levels (130, 160 or 180 g CP/kg DM), while in experiment 2, the treatments consisted of three levels of rumen degradable protein (RDP; 80, 100 or 120 g RDP/kg DM) in diets with average of 163 g CP/kg DM. Variables evaluated in both experiments were dry matter intake (DMI), total apparent digestibility, milk yield (MY) and composition, ruminal fermentation and N balance. In experiment 1, the increase of CP from 130 to 180 linearly increased the organic matter, CP, neutral detergent fiber (NDF) and acid detergent fiber (ADF) intake (kg) and the apparent total digestibility coefficient of DM and CP. In addition, a linear increase of MY, fat corrected milk (FCM) and daily production of fat, protein, lactose, casein and total solids was observed. A linear increase in ruminal ammoniacal nitrogen (NH3-N) concentration and nitrogen excretion in milk, feces and urine was also observed. However, there was no observed effect on SCFA concentration. In experiment 2, the increase of the RDP from 80 to 120 increased the DMI, MY, FCM, milk protein content and digestibility coefficient of the NDF, ADF and ethereal extract. Additionally, there was an increase in NH3-N concentration and milk nitrogen excretion. The studies indicated that the increase of CP content up to 100 g RDP/kg DM increased the DMI and the productive performance of the cows, but also increased urine N. Thus, it is desirable that the increase of the CP through the increase of the RDP is carried out up to 100 g of RDP/kg DM, since there is elimination of nitrogen, decrease of milk yield and decrease of propionic acid in values above that level.